Learning Concepts in Technology and Engineering : The Disciplinary Basis of T and E in STEM - Vries, Marc J. de, (Educational Research E-Books Online, Collection 2025., 2025)
Technology education has developed from a craft-oriented subject to a richer, partly cognitive subject. For this latter part, a disciplinary basis is needed. Furthermore, the disciplinary basis for the T has to be seen more and more in the context of the disciplinary basis for the other STEM subjects. This book offers such a disciplinary basis. It can be used for curriculum development, research and teaching. The book brings together insights from philosophy of technology about the meaning of the various concepts that form the disciplinary basis and pedagogical insights into learners' possible preconceptions as well as strategies to teach and learn these concepts.